EVALUASI LAYANAN DIGITAL PENGURUSAN SURAT IZIN MENGEMUDI KEPOLISIAN NEGARA REPUBLIK INDONESIA - Nurhafidah Nurhafidah; Muhammad Lutfi; Muhammad Takdir (Universitas Bina Taruna Gorontalo, 2024)
This research aims to find out whether this application makes things easier for people or makes things more difficult for people. The National Police must be able to keep up with technological advances so that it makes it easier to serve the public. One of the police regulations is the Police Traffic Corps Digital Application which was available on April 13 2021. This is the official application of the Indonesian Police Corps. The method used in this research is qualitative with a case study approach. Data sources come from trusted and credible online portals such as CNN Indonesia, Tribun.news, Kompas.com, Tempo.com and relevant journal articles. The results of this research are that the National Police traffic police digital application cannot yet be used optimally because it is still in the development process, and many of its features are still not active.